2021
DOI: 10.1109/tnse.2021.3107529
|View full text |Cite
|
Sign up to set email alerts
|

Learning Concept Interestingness for Identifying Key Structures From Social Networks

Abstract: Identifying key structures from social networks that aims to discover hidden patterns and extract valuable information is an essential task in the network analysis realm. These different structure detection tasks can be integrated naturally owing to the topological nature of key structures. However, identifying key network structures in most studies has been performed independently, leading to huge computational overheads. To address this challenge, this paper proposes a novel approach for handling key structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Gao et al [32] suggested the employment of graph topological metrics for node ranking and neighborhood inflation for seed selection. Lastly, Gao et al [22] utilized formal context methods for the selection of local key structures.…”
Section: A Seed Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gao et al [32] suggested the employment of graph topological metrics for node ranking and neighborhood inflation for seed selection. Lastly, Gao et al [22] utilized formal context methods for the selection of local key structures.…”
Section: A Seed Selectionmentioning
confidence: 99%
“…In addition, two key operations were defined for extracting the common attributes/public objects for a given set of objects/attributes. In recent years, many scholars have successfully integrated FCA with specific tasks such as data mining [15], machine learning [16], [17], [18], knowledge discovery [19], [20], cloud computing [21], complex network [22], [23], [24], [25], and so on.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In computer science, some studies were successful to apply formal concept analysis for solving some problems in many sub-domains, e.g ., datamining ( Aragón, Medina & Ramírez-Poussa, 2022 ; Hao et al, 2023 ), machine learning ( Janostik, Konecny & Krajča, 2022 ), data science ( Bazin et al, 2022 ), intelligent system ( Shao et al, 2023 ), information retrieval ( Ojeda-Hernández, López-Rodríguez & Mora, 2023 ; Khattak et al, 2021 ), natural language processing ( Marín et al, 2021 ; Jain, Seeja & Jindal, 2020 ), decision support system ( Wei et al, 2020 ), recommendation system ( Liu et al, 2022 ), semantic web ( Jindal, Seeja & Jain, 2020 ), cloud computing ( Khemili, Hajlaoui & Omri, 2022 ), data structure ( Ferré & Cellier, 2020 ), mobile application ( Kwon et al, 2021 ), software engineering ( Carbonnel et al, 2020 ), and robotic ( Zhang et al, 2023 ). In addition, some successful studies to apply formal concept analysis were in other domains, e.g ., engineering ( Rocco, Hernandez-Perdomo & Mun, 2020 ), mathematics ( Jäkel & Schmidt, 2022 ; Rocco, Hernandez-Perdomo & Mun, 2020 ), biology ( Gély et al, 2022 ), psychology ( Belohlavek & Mikula, 2022 ), medicine ( Md Saleh, Ab Ghani & Jilani, 2022 ), business ( Wajnberg et al, 2018 ; Ravi, Ravi & Prasad, 2017 ; Acharjya & Das, 2017 ), and social science ( Lang & Yao, 2023 ; Hao et al, 2021 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tey help people gather, communicate, and share their common interests [4]. Multiple social network platforms, such as Facebook, Twitter, Sina Weibo, and a few e-mail systems [5], allow users to access various services simultaneously [6,7]. Te use of online platforms is exponentially amplifed, which increases the risk of information leakage and opens the door to several cybercrimes due to the large amount of data and information available on these online platforms [8,9].…”
Section: Introductionmentioning
confidence: 99%